Counseling Activities and Early Detection of Low Back Pain Cases with Farmers Group of Rukun Sentosa 1 Ngemplak Boyolali - Nur Rachmat; Bambang Kuncoro; Fadhila Firmanurulita (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Farming is a job that is mostly done by people in Boyolali. Low back pain in farmers often occurs because of the working position carried out by farmers, namely bending over. The use of a lumbar corset can reduce low back pain in farmers. The purpose of community service at the Rukun Sentosa Ngesrep 1 Ngemplak Boyolali Farmer Group is to empower farmers to know about early detection, prevention and treatment of low back pain that is often experienced by farmers. The activity is carried out in three months starting from May 31, 2021 to August 10, 2021. The stages of activity are preparation, implementation and evaluation. Preparation is carried out by conducting a preliminary survey to see conditions in the field and obtaining permits for activities in farmer groups. The implementation is carried out by empowerment in the form of counseling in the form of discussions with farmer groups, detection of farmers who experience pain, and giving a Lumbar Corset. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of activity. The result of the activity is the implementation of counseling and early detection of low back pain to farmers and providing a lumbar corset to be used by farmers to reduce back pain when farming. Implementing the activities of lecturers and students and assisted by the management and members of the Rukun Sentosa Ngesrep 1 Ngemplak Boyolali farmer group.